Determination of Metabolic Syndrome among North Indian Adolescents - Riyaz Ahmad Bhat; Irshad Paray; Showkat Zargar; Ashraf Ganie; Imran Khan (Current Overview on Disease and Health Research Vol. 4, 2022)
The present study aimed to estimate the prevalence of MS using pediatric International Diabetic Federation (IDF) definition and compare it with estimates of Adult Treatment Panel III (ATP III) definition among adolescents in Northern India. The onset of metabolic syndrome (MS) in children and adolescents is significantly increased by childhood obesity. Studies are required to determine the incidence of these metabolic abnormalities in the teenage population due to the significant prevalence of insulin resistance and MS in the Indian adult population. At a total of 899 adolescents attending school (aged 10-18 years) participated in this population-based prospective study. All the clinical and biochemical assessment were done after proper consent. The MS was determined by the National Cholesterol Education Program ATP III definition modified for age and pediatric IDF definition. The prevalence of MS was 3.5% according to ATP III criteria and 1.5% based on IDF criteria. No significant gender difference was observed in the distribution of MS. Hypertriglyceridemia was the most common and abdominal obesity the least common constituent of MS. This study provides the first estimates of MS using pediatric IDF definition in the adolescent population from Northern India. Immediate lifestyle modifications are needed to control the obesity epidemic and its metabolic consequences. Furthermore, research is needed to know the effects of puberty on obesity and its late consequences.